2021
DOI: 10.3390/jtaer16060120
|View full text |Cite
|
Sign up to set email alerts
|

Research on Influencing Factors of Service Interactive Experience of Digital Gas Station—The Case from China

Abstract: A series of digital marketing transformations have been carried out at Chinese gas stations. From the perspective of user experience, the article discovers the problems in the digital service system of gas stations. Through semi-structured interviews, we collect consumers’ actual usage of digital equipment and service systems. The research adopts grounded theory to encode qualitative data. The behavioral state and psychological needs of consumers in the driving situation are analyzed. The study clarifies the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…1) On the other hand, this study was unable to predict the behavior and requirements of food-service providers and visitors in advance. Therefore, it is necessary to use the exploratory Grounded Theory and conduct in-depth interviews to uncover the underlying elements and relationships [52].…”
Section: Grounded Theorymentioning
confidence: 99%
“…1) On the other hand, this study was unable to predict the behavior and requirements of food-service providers and visitors in advance. Therefore, it is necessary to use the exploratory Grounded Theory and conduct in-depth interviews to uncover the underlying elements and relationships [52].…”
Section: Grounded Theorymentioning
confidence: 99%
“…(1) On the other hand, this study was unable to predict the behavior and requirements of food-service providers and visitors in advance. Therefore, it is necessary to use the exploratory Grounded Theory and conduct in-depth interviews to uncover the underlying elements and relationships [55]. (2) Procedural grounded theory often uses purposive sampling, which is consistent with the purpose of our study [56].…”
Section: Grounded Theorymentioning
confidence: 99%
“…In general, it is observed that when adapting the new technology, the role of the SI is much higher. When deciding whether or not to buy things online, the customers give the opinions of previous customers [61], and digitalisation has benefited many businesses in enhancing their profitability [62]. Similarly, this is observed in Saudi Arabia where the technology adaption by the consumers is influenced by many factors [63][64][65].…”
Section: Simentioning
confidence: 99%